1989
DOI: 10.2307/1940209
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value of Hypogeous Fungus for a Forest‐Dwelling Ground Squirrel

Abstract: Hypogeous fungi often contain high concentrations of nitrogenous compounds, vitamins, and minerals and are major dietary items for many rodents and other small mammals in North American forests. For these reasons ecologists have presumed hypogeous fungi to be of high nutritional value for small mammals. In a series of feeding experiments we investigated the nutritional quality of sporocarps (fruiting bodies) of the hypogeous fungus Elaphomeyces granulatus in the diet of the golden—mantled ground squirrel Sperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
2
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 30 publications
1
75
2
2
Order By: Relevance
“…For example, Johnson [9] reported that the sporocarps of the genus Elaphomyces were common in the study area but their spores were comparatively rare in the small mammal pellets. The aroma of Elaphomyces is rather faint comparing with other hypogeous species [9] and the digestible energy content is low compared with that of conifers seeds [8]. Moreover, Elaphomyces have a powdery spore mass and are likely to be discarded by small mycophagists, which focus on eating the thick peridium [7].…”
Section: Fungal Taxamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Johnson [9] reported that the sporocarps of the genus Elaphomyces were common in the study area but their spores were comparatively rare in the small mammal pellets. The aroma of Elaphomyces is rather faint comparing with other hypogeous species [9] and the digestible energy content is low compared with that of conifers seeds [8]. Moreover, Elaphomyces have a powdery spore mass and are likely to be discarded by small mycophagists, which focus on eating the thick peridium [7].…”
Section: Fungal Taxamentioning
confidence: 99%
“…Ectomycorrhizal hypogeous fungi form below-ground sporocarps, so they rely on mycophagous animals for spore dispersal [3]. Although the digestible energy content of hypogeous fungi is lower compared with that of seeds and other foodstuff, for some small mammals the hypogeous sporocarps could be a main dietary source [3,[7][8][9]. Consumed spores remain viable after the passage through the mammal gut and could successfully inoculate the roots of mycorrhizal plants.…”
Section: Introductionmentioning
confidence: 99%
“…La información acerca del consumo de hongos por mamíferos es escaso y fueron Fogel y Trappe quienes en 1976 mencionan este hecho (Cork & Kenagi, 1989) y aunque es poco lo que se conoce acerca de los patrones de micofagia de estos organismos, trabajos realizados en Australia muestran que cerca de 30 especies de mamíferos consumen hongos (Claridge et al, 1996); los hábitos micofágicos aparecen en especies de 11 familias de pequeños roedores (Muridae) y ratas Tabla 2. Entomofauna asociada a los macrohongos de la región del Medio Caquetá (U= Uitoto, A= Andoke, M= Muinane).…”
Section: -Mamíferos Micófagosunclassified
“…Se ha encontrado que algunas especies de ardillas incluyen en su dieta una gran variedad de recursos, incluyendo pequeños frutos, flores, corteza y látex de troncos, hojas nuevas, hongos, insectos y huevos de ranas (Cork & Kenagi, 1989;Giacalone, 1997). En este estudio, los indígenas reportaron el consumo de hongos por Microsciurus flaviventer, una ardilla llamada Nopi (U), Tyityio (M) y I'x'siko (A) y aunque no fue posible observarla consumiendo hongos, todos los indígenas consultados lo mencionaron.…”
Section: -Mamíferos Micófagosunclassified
“…Members of the family Sciuridae (mainly tree squirrels and chipmunks) are the most frequently observed mammalian mycophagists (Fogel and Trappe 1978). The availability and variety of fungi, including truffles, in forest ecosystems when in season and the minimal foraging efforts needed to locate them are what make fungal fruiting bodies a common and valuable food source to sciurids (Cork and Kenagy 1989;Maser et al 2008). The American Red Squirrel (Tamiasciurus hudsonicus Erxleben) alone has been documented eating 89 species of fungi (Fogel and Trappe 1978), and it is well known that the American Red Squirrel, along with other tree squirrels, dries fungi in tree branches or in the sun before storing them elsewhere (Fogel and Trappe 1978;Lurz and South 1998;Vernes and Poirier 2007;Maser et al 2008).…”
mentioning
confidence: 99%